The Three Billy Goats Gruff - Yates, Irene (Ladybird Books Ltd, 1999)
Based on the traditional fairy tale 'The Three Billy Goats Gruff', this vibrantly illustrated story is sure to become a favourite in every home. Part of the Ladybird 'First Favourite Tales' series - a perfect introduction to fairy tales for preschoolers - this story contains lots of funny rhythm and rhyme to delight young children. Ideal for reading aloud and sharing with 2-4 year olds.
Keywords: Juvenile Fiction; Short Stories